THE IMPACT OF DESTINATION IMAGE AND FACILITIES ON INTEREST IN REVISITING - Cut Sukmawati; Novi Cyntiani Hasibuan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examines the impact of destination image and facilities on repeat visit interest at the Syakirah The View Sibiobio tourist attraction in South Tapanuli Regency. 100 respondents were selected for this quantitative research study using non-probability sampling with incidental sampling techniques. Data was collected through surveys, and multiple linear regression analysis was conducted using the SPSS 25.0 software program. The findings reveal that the destination image variable does not have a positive and significant impact on repeat visit interest when considered individually. However, facility variables do have a positive and significant impact on repeat visit interest when considered individually. Furthermore, when both destination image and facilities are considered together, they have a positive and significant impact on repeat visit interest. These findings provide valuable insights for managers and stakeholders of the Syakirah The View Sibiobio tourist attraction to enhance repeat visit interest by focusing on improving facilities and creating a strong destination image.